Toward Holistic Workplace Health: Integrating Ergonomics, Nutrition, Herbal Medicine, and Self-Acupressure for Shoulder Pain Prevention Among Manufacturing Workers - Alya Kamilah; Nurul Inayah; Devany Rafika Anggraini; Sabitah Naura Eka Putri; Tita Mutia Rachma; Siti Fatimah Azzahra; Reza Akni Arifia; Dela Fadlilatul Arofa; Damayanti Nurmu’arofatun Ningtiyas; Dwi Setiani Sumardiko; Edith Frederika Puruhito (Inovasi Lokal, 2026)
Background: Work-related shoulder pain remains one of the leading musculoskeletal disorders among manufacturing workers, resulting in impaired productivity, reduced functional capacity, and increased occupational health burden. Existing workplace education primarily emphasizes ergonomics, while integrated self-management approaches incorporating nutrition, complementary medicine, and self-care techniques remain underexplored. This study evaluated the effectiveness of a holistic educational intervention for improving workers' knowledge of shoulder pain prevention and self-management. Methods: A community-based one-group pre-test–post-test study was conducted among 20 workers from a plywood manufacturing industry in East Java, Indonesia. Participants attended a 90-minute educational program integrating occupational health education, ergonomic practices, nutritional counseling, herbal education using turmeric (Curcuma longa) and tamarind (Tamarindus indica), and guided self-acupressure.  Results: All participants completed the intervention (response rate: 100%). The mean knowledge score increased from 4.5 at baseline to 9.4 after the intervention, representing an average improvement of 4.9 points. Every participant demonstrated higher post-test scores, with individual improvements ranging from 1 to 8 points. Before the intervention, 60% of participants had poor knowledge, 25% had fair knowledge, and 15% had good knowledge.  Conclusions: The holistic educational intervention effectively enhanced workers' knowledge regarding shoulder pain prevention and self-management. The principal novelty of this study is the introduction of a Holistic Occupational Self-Management Framework, integrating occupational health education, ergonomics, nutrition, herbal medicine, and self-acupressure into a unified worker-centered model. This framework provides a foundation for future technology-enabled occupational health programs aimed at promoting sustainable prevention of work-related musculoskeletal disorders.